2022
DOI: 10.3389/fonc.2022.864046
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Potential Mechanisms of Acupoint Stimulation Combined With Chemotherapy in Combating Cancer: A Review and Prospects

Abstract: Although chemotherapy is the first-line treatment strategy for a variety of tumors, its side effects have limited its efficacy. This review summarizes the progress on the use of acupoint stimulation to combat chemotherapy-associated side effects, including chemotherapy-induced peripheral neuropathy (CIPN), cognitive impairment (CICI), and gastrointestinal toxicity (GI), as well as myelosuppression and immunosuppression. It was found that acupoint stimulation attenuated CIPN and GI by modulating the 5-hydroxytr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Exploration of the combination NPs with classical chemotherapeutic agents may be a possible way to enhance the susceptibility of cancer cells. Moreover, a study ( Li et al, 2022 ) suggests that acupoint stimulation involves synergy with chemotherapy and can alleviate chemotherapeutic agents side effects.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Exploration of the combination NPs with classical chemotherapeutic agents may be a possible way to enhance the susceptibility of cancer cells. Moreover, a study ( Li et al, 2022 ) suggests that acupoint stimulation involves synergy with chemotherapy and can alleviate chemotherapeutic agents side effects.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Studies demonstrated that acupuncture improved symptoms through systemic conditioning of meridians and acupoints ( 9 ). It achieved systemic or local responses by local acupuncture around superficial tumors ( 10 ). Additionally, it had a positive therapeutic impact on a range of immunological disorders linked to tumors and could significantly enhance the capacity to fight infections ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these immunosuppressive cells, TAMs represent the major tumor-infiltrating immune cell populations. 16–18 TAMs can be divided into M1-like and M2-like phenotypes, playing antitumor and protumor roles, respectively. Accumulating studies reveal that the TME usually has a predominate presence of M2-like TAMs that can lead to immunosuppression and chemoresistance.…”
Section: Introductionmentioning
confidence: 99%